Structuralism In Jane Eyre: Interaction Of Binary Oppositions In Buildungsroman - Shruti Sharma (CEMJP, 2024)
This paper explores Jane Eyre by Charlotte Brontë via a structuralist perspective, paying special attention to the idea of binary oppositions and how they help Jane navigate the constraints of Victorian society and develop her identity. By carefully dissecting these conflicting components that keep coming up, the study seeks to reveal the societal commentary that is subtly present in the story. The study will break down the novel's key binary oppositions. These contrast the desire for freedom (Lowood/Moor House) with the actual confining areas (Gateshead/Thornfield). We will examine how these disparate environments symbolize the social and physical restrictions that women face. The dichotomy of agency connected with the masculine domain and passivity associated with the feminine sphere will also be analyzed in light of Jane's interactions with Mrs. Reed and Mr. Rochester, among other characters. Here, we shall witness Jane's brilliance, tenacity, and steadfast spirit as she defies these accepted standards. The relevance of recurrent motifs and symbols within the narrative framework will also be covered in this session. For example, the investigation of fire and light will be examined as metaphors for Jane's own emerging self-reliance and curiosity. This symbolism will be contrasted with the darkness and entrapment symbolized by confining spaces like Gateshead, where Mrs. Reed embodies the oppressive nature of Victorian expectations. Utilizing a structuralist methodology, the essay will contend that Jane Eyre is more than just a tale of coming-of-age. It develops into a powerful indictment of women's limitations and Victorian societal conventions. The story promotes the search of self-discovery and individual autonomy, especially in the face of oppressive society limits, via Jane's unrelenting defiance of the established binaries. This disobedience becomes a challenge to the fundamentals of a constrictive social structure rather than just a personal conflict. In addition to examining how these binary choices affect Jane, the study will also look at how they influence the story as a whole. The recurring pattern of Jane's experiences—from imprisonment to a brief moment of optimism, then back to another setback—can be interpreted as a mirror of the cyclical nature of the social norms that she consistently challenges. In the end, the essay will make the case that reading Jane Eyre via a structuralist lens reveals a nuanced and intricate story. It is a story of personal growth intertwined with a powerful social commentary, all masterfully woven through the utilization of binary oppositions and symbolic motifs.